Praticas docente: memórias entre a educação básica e a universidade - GONÇALVES, Raimundo Pinheiro (2024)
The present work aims to reflect on my personal, academic, professional and academic trajectory rescuing the historical facts, involving my experiences, passing through childhood where some factors such as jokes, family values contributed to my development in several aspects of changes and Transformations. I felt the need to deepen my knowledge and knowledge acquired through studies and experiences with colleagues, teachers and all subjects involved in education in several stages, assuming responsibilities that certainly contributed to the insertion in teaching in the municipality of Abaetetuba. Starting from a bibliographical review, as well as the discussions and socialized reflections with the interdisciplinary disciplines during the course of pedagogy. This research of qualitative approach has as method the life history or (auto) biographical method that expressed the writing of the own life. Thus the writing of the narrative was mobilized from an awareness, becoming clear my knowledge of the intuitive, personal and political dimensions referring to the constant challenges in relation to the experiences and the positions taken.